2014
DOI: 10.1111/ene.12472
|View full text |Cite
|
Sign up to set email alerts
|

Orolingual angioedema after alteplase therapy of acute ischaemic stroke: incidence and risk of prior angiotensin‐converting enzyme inhibitor use

Abstract: The incidence of rt-PA-related OA in the Asian population is lower than that in the Caucasian population. Pre-stroke use of ACE inhibitors significantly increases the risk of this complication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 26 publications
1
43
1
Order By: Relevance
“…Prevalence of OA in patients with acute ischemic stroke treated with alteplase was 4.9%, which is in accordance to previous studies [1][2][3][4]7]. We found no significant differences in the frequency of insular cortex ischemic lesions on pre-thrombolysis CT, and early signs of insular cortex ischemia were not independent predictors of OA occurrence in multivariate analysis.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Prevalence of OA in patients with acute ischemic stroke treated with alteplase was 4.9%, which is in accordance to previous studies [1][2][3][4]7]. We found no significant differences in the frequency of insular cortex ischemic lesions on pre-thrombolysis CT, and early signs of insular cortex ischemia were not independent predictors of OA occurrence in multivariate analysis.…”
Section: Discussionsupporting
confidence: 91%
“…Other case control-studies found a higher frequency of OA in women [3,5] and, in our study, female sex was an independent risk factor for OA, which is in accordance to a large cohort study of medication-related angioedema incidence [9]. The reason for this sex difference is not clear, but may include the influence of sex hormones on the regulation of inflammation and an increased T h 2 immune response in women [10], which is further supported by the female predominance of chronic urticaria, a condition with a pathophysiology closely linked to acquired angioedema [11].…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations